Patent foramen ovale presenting as visual loss. (December 2016) - Liu, Xiaoxuan; Calvert, Patrick A; Arif, Sayqa; Keane, Pearse A; Denniston, Alastair K
Retinal artery occlusion in an otherwise healthy, young patient is rare. In this context it is important to consider patent foramen ovale as a differential. Early referral to a cardiology specialist for diagnosis and treatment is important for preventing further ocular and non-ocular events.